A Survey on Multisensor Fusion and Consensus Filtering for Sensor Networks - Hu, Jun; Ma, Lifeng; Wei, Guoliang; Wang, Zidong; Li, Wangyan; Ding, Derui (Discrete Dynamics in Nature and Society, 2015)
Multisensor fusion and consensus filtering are two fascinating subjects in the research of sensor networks. In this survey, we will cover both classic results and recent advances developed in these two topics. First, we recall some important results in the development of multisensor fusion technology. Particularly, we pay great attention to the fusion with unknown correlations, which ubiquitously exist in most of distributed filtering problems. Next, we give a systematic review on several widely used consensus filtering approaches. Furthermore, some latest progress on multisensor fusion and consensus filtering is also presented. Finally, conclusions are drawn and several potential future research directions are outlined.